Structure-Based Evolution of Subtype-Selective Neurotensin Receptor Ligands - Schaab, Carolin; Kling, Ralf; Einsiedel, Jürgen; Hübner, Harald; Clark, Timothy; Seebach, Dieter; Gmeiner, Peter (ChemistryOpen, 2014)
Subtype-selective agonists of the neurotensin receptor NTS2 represent a promising option for the treatment of neuropathic pain, as NTS2 is involved in the mediation of m-opioid-independent anti-nociceptive effects. Based on the crystal structure of the subtype NTS1 and previous structure-activity relationships (SARs) indicating a potential role for the sub-pocket around Tyr11 of NT(8-13) in subtype-specific ligand recognition, we have developed new NTS2-selective ligands. Starting from NT(8-13), we replaced the tyrosine unit by β2-amino acids (type 1), by heterocyclic tyrosine bioisosteres (type 2) and peptoid analogues (type 3). We were able to evolve an asymmetric synthesis of a 5-substituted azaindolylalanine and its application as a bioisostere of tyrosine capable of enhancing NTS2 selectivity. The S-configured test compound 2a, [(S)-3-(pyrazolo[1,5-α]pyridine-5-yl)-propionyl11]NT(8-13), exhibits substantial NTS2 affinity (4.8 nm) and has a nearly 30-fold NTS2 selectivity over NTS1. The (R)-epimer 2b showed lower NTS2 affinity but more than 600-fold selectivity over NTS1.
UnivIS-Import:2015-03-09:Pub.2014.nat.dchph.lphch.struct